The Redox Activity of Protein Disulfide Isomerase Inhibits ALS Phenotypes in Cellular and Zebrafish Models - Sonam Parakh; Sina Shadfar; Emma R. Perri; Audrey M.G. Ragagnin; Claudia V. Piattoni; Mariela B. Fogolín; Kristy C. Yuan; Hamideh Shahheydari; Emily K. Don; Collen J. Thomas; Yuning Hong; Marcelo A. Comini; et al. (iScience, 2020)
Summary: Pathological forms of TAR DNA-binding protein 43 (TDP-43) are present in almost all cases of amyotrophic lateral sclerosis (ALS), and 20% of familial ALS cases are due to mutations in superoxide dismutase 1 (SOD1). Redox regulation is critical to maintain cellular homeostasis, although how this relates to ALS is unclear. Here, we demonstrate that the redox function of protein disulfide isomerase (PDI) is protective against protein misfolding, cytoplasmic mislocalization of TDP-43, ER stress, ER-Golgi transport dysfunction, and apoptosis in neuronal cells expressing mutant TDP-43 or SOD1, and motor impairment in zebrafish expressing mutant SOD1. Moreover, previously described PDI mutants present in patients with ALS (D292N, R300H) lack redox activity and were not protective against ALS phenotypes. Hence, these findings implicate the redox activity of PDI centrally in ALS, linking it to multiple cellular processes. They also imply that therapeutics based on PDI's redox activity will be beneficial in ALS.